Let's solve your equation step-by-step.
25m+100−24m−75=68
Step 1: Simplify both sides of the equation.
25m+100−24m−75=68
25m+100+−24m+−75=68
(25m+−24m)+(100+−75)=68(Combine Like Terms)
m+25=68
m+25=68
Step 2: Subtract 25 from both sides.
m+25−25=68−25
m=43
Answer:
m=43
Answer:
Once
Step-by-step explanation:
8 can only go into 9 once, if you were to do it a second time, there would be a remainder of 7.
It would be 10x5 + 3x8= 74
answer
10
step-by-step explanation
the equation given is sin(x) = cos(y) with x = 2k + 3 and y = 6k + 7
substitute in 2k+ 3 for x in sin(x) and substitute in 6k + 7 for y in cos(y)
sin(x) = cos(y)
sin(2k + 3) = cos(6k + 7)
we know that sin(x) = cos(90 -x)
sin(2k + 3)
= cos(90 - (2k + 3) )
= cos(90 - 2k - 3)
= cos(87 - 2k)
substitute this into the equation sin(2k + 3) = cos(6k + 7)
sin(2k + 3) = cos(6k + 7)
cos(87 - 2k) = cos(6k + 7)
87 - 2k = 6k +7
80 = 8k
k = 10
The answer would be 3 hope helps